Pengaruh Struktur Modal, Ukuran Perusahaan, Pertumbuhan Perusahaan, Profitabilitas Dan Leverage Terhadap Nilai Perusahaan Pada Perusahaan Pertambagan Yang Terdaftar Di Bursa Efek Indonesia - Karim, Kartiwi; Jeandry, Gregorius; Syahdan, Rinto (Innovative: Journal Of Social Science Research, 2024)
This study aims to examine the effect of capital structure, company size, growth, profitability, and leverage on the firm value of mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. By adopting a quantitative approach, this research employs a purposive sampling method, resulting in 135 observations. Data analysis is conducted using panel data regression with a fixed effects model. The findings indicate that company size and leverage have a significant impact on firm value, while capital structure, growth, and profitability do not show a significant effect. The positive relationship between company size and value suggests that larger companies enjoy higher valuations due to their better access to external capital and more effective asset management. Conversely, high leverage tends to increase firm value as it is seen as a signal of financial stability for investors. However, the lack of a significant impact from capital structure, growth, and profitability implies that other factors play a more influential role in determining firm value within the Indonesian mining sector.